2013
DOI: 10.1016/j.socscimed.2012.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Financial burden of household out-of pocket health expenditure in Viet Nam: Findings from the National Living Standard Survey 2002–2010

Abstract: In Viet Nam, household direct out-of-pocket (OOP) health expenditure as a share of the total health expenditure has been always high, ranging from 50% to 70%. The high share of OOP expenditure has been linked to different inequity problems such as catastrophic health expenditure (households must reduce their expenditure on other necessities) and impoverishment. This paper aims to examine catastrophic and poverty impacts of household out-of-pocket health expenditure in Viet Nam over time and identify socio-econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
156
5
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(194 citation statements)
references
References 7 publications
22
156
5
11
Order By: Relevance
“…However, after nearly 20 years of implementation and continuous amendments, a number of studies have indicated the modest benefits of health insurance in helping patients away from catastrophe of medical expense. [22][23][24] In fact, out-of-pocket payment was too high 23 and no statistically significant effect of health insurance on the level of out-of-pocket payment was found. In addition, payments, Nguyen 22 did not find any.…”
Section: Discussionmentioning
confidence: 93%
“…However, after nearly 20 years of implementation and continuous amendments, a number of studies have indicated the modest benefits of health insurance in helping patients away from catastrophe of medical expense. [22][23][24] In fact, out-of-pocket payment was too high 23 and no statistically significant effect of health insurance on the level of out-of-pocket payment was found. In addition, payments, Nguyen 22 did not find any.…”
Section: Discussionmentioning
confidence: 93%
“…The incidence of CHE among households with cancer patients in South Korea was 39.8%, lower than that of CHE in China 7. Besides CHE among cancer patients, a study in Vietnam showed that the number of households with CHE and impoverishment increased during the period of 2002‐2010 25. In Nepal, about 14% households were faced with CHE 26…”
Section: Discussionmentioning
confidence: 99%
“…Overall in lower and middle income countries, health care expenditure accounts for between 13 to 32% of household expenditures, with one in four poor households in low income countries incurring potentially catastrophic health care expenses when family members become ill [11]. Between 41% and 56% of households in these countries spend 100% of health care expenditures on drugs [11][12][13][14]. We did not include Brazil and China, for example, because the nature of inappropriate use, including drivers,' is still surfacing in its detail.…”
Section: Approachmentioning
confidence: 99%